2015
DOI: 10.1016/j.pocean.2015.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Winter use of sea ice and ocean water mass habitat by southern elephant seals: The length and breadth of the mystery

Abstract: Winter use of sea ice and ocean water-mass habitat by southern elephant seals: The length and breadth of the mystery, Progress in Oceanography (2015), doi: http://dx.doi.org/ 10. 1016/j.pocean.2015.05.023 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
89
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 41 publications
(97 citation statements)
references
References 97 publications
8
89
0
Order By: Relevance
“…This study follows on from previous work on Kerguelen SESs during winter, showing that adult females were closely associated within the marginal sea ice zone, following the northward sea ice extension, and foraging in highly concentrated sea ice close to the sea ice edge Hindell et al, 2016;Labrousse et al, 2015). In contrast, it was shown that sub-adult males remained deep within the sea ice foraging mainly over the Antarctic shelf or within the Antarctic Slope Front (ASF) in sea ice of intermediate concentration.…”
Section: Introductionsupporting
confidence: 72%
See 4 more Smart Citations
“…This study follows on from previous work on Kerguelen SESs during winter, showing that adult females were closely associated within the marginal sea ice zone, following the northward sea ice extension, and foraging in highly concentrated sea ice close to the sea ice edge Hindell et al, 2016;Labrousse et al, 2015). In contrast, it was shown that sub-adult males remained deep within the sea ice foraging mainly over the Antarctic shelf or within the Antarctic Slope Front (ASF) in sea ice of intermediate concentration.…”
Section: Introductionsupporting
confidence: 72%
“…For these individuals, the section of tracks where animals travelled again south within the sea ice region (one female and two males) after their return to the colony were removed from analysis. Details of the instrumentation, seal handling and data processing for filtering ARGOS positions are provided by Labrousse et al (2015). An average of 18.1 ± 8.6 tag positions were transmitted via the ARGOS system each day.…”
Section: Animal Handling Deployment Data Collection and Filteringmentioning
confidence: 99%
See 3 more Smart Citations